2013
DOI: 10.4254/wjh.v5.i10.568
|View full text |Cite
|
Sign up to set email alerts
|

Presence of disease specific autoantibodies against liver sinusoidal cells in primary biliary cirrhosis

Abstract: AIM:To investigate the presence of autoantibodies directed against liver sinusoidal cells in primary biliary cirrhosis (PBC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(41 reference statements)
1
2
0
Order By: Relevance
“…Endothelins also cause contraction of stellate cells thus helping in the early appearance of portal hypertension in PBC [188] . In agreement with this hypothesis are findings from our group indicating that disease specific antibodies against liver sinusoidal cells circulate in PBC [189] . In addition we reported that polymorphisms related to endothelial cells were associated with PBC.…”
Section: Pathogenesis Of Pbc: a Unifying Hypothesissupporting
confidence: 88%
“…Endothelins also cause contraction of stellate cells thus helping in the early appearance of portal hypertension in PBC [188] . In agreement with this hypothesis are findings from our group indicating that disease specific antibodies against liver sinusoidal cells circulate in PBC [189] . In addition we reported that polymorphisms related to endothelial cells were associated with PBC.…”
Section: Pathogenesis Of Pbc: a Unifying Hypothesissupporting
confidence: 88%
“…An understanding of the endothelial system is essential to appreciating normal physiology but also disease processes. Changes in LSEC composition have been observed in a number of conditions such as hepatic fibrosis 3 , autoimmune disease 4 , and viral hepatitis 5 . A map of the endothelial structures in the normal liver is essential to appreciate the structural and molecular changes that take place in diseases of the liver.…”
mentioning
confidence: 99%
“…Changes in LSEC composition have been observed in a number of conditions such as hepatic fibrosis 3 , autoimmune disease 4 , and viral hepatitis 5 . A map of the endothelial structures in the normal liver is essential to appreciate the structural and molecular changes that take place in diseases of the liver.…”
Section: As Well As Systemic Vascular Endothelial Cells the Liver Hamentioning
confidence: 99%